SOSIALISASI PARTISIPATIF GURU SOSIOLOGI DALAM MENINGKATKAN KEDISIPLINAN SISWA KELAS XI IPS 1 SMA NEGERI 1 TELUK KERAMAT - Sari, Pamela; Bahari, Yohanes; Asriati, Nuraini (Universitas Tanjungpura, 2022)
This study aims to determine the form of participatory socialization of sociology teachers in improving the discipline of class XI IPS 1 students at SMA Negeri 1 Teluk Keramat, Sambas Regency. Researchers used descriptive research methods with qualitative research forms. The data sources for this study were the sociology teacher, BK teacher, and six students of class XI IPS 1. The results showed that participatory socialization of sociology teachers in improving the discipline of class XI IPS 1 students of SMA Negeri 1 Teluk Keramat by giving symbolic rewards. Giving rewards for good behavior in the form of praise as a form of teacher appreciation for students, communication as interaction, namely communication that exists between teachers and students directly and face to face, verbal communication with oral and written so that it is easily understood by students, student-centered socialization, and students' learning needs are taken into account.